ALASAN PEMILIHAN MAKANAN, AKSES PEMBELIAN MAKANAN, DAN KUALITAS DIET PADA MAHASISWA - Yugharyanti, Tsamara Putri; Fatimah, Siti; Rahfiludin, Mohammad Zen (Journal of Nutrition College, 2024)
ABSTRACTBackground: The diet of Indonesian people has changed due to the influence of the globalization era and technological advances. Inappropriate dietary changes such as excessive consumption of foods containing sugar, salt and fat increase the risk of obesity. Obesity cases in Central Java Province have increased from 2019 (5.5%) to 2021 (6.8%). A person's diet can affect the quantity and quality of food consumed, thus affecting the quality of the diet.Objective: This study aims to analyze the correlation food choice and food purchase access with diet quality among Public Health students at Diponegoro University.Methods: This type of research was observational study with cross sectional design. The subjects were 100 students of Faculty of Public Health Diponegoro University. The subjects were selected by simple random sampling. The independent variables were food selection and food purchase access. The confounding variables were nutritional knowledge and culture. Diet quality data was taken from the results of the Semi Quantitative Food Frequency Questionnaire which was converted to a diet quality score. Correlation analysis used the Spearman Rank test.Results: The results showed that the subjects had good diet quality 55% and poor diet quality 45%. Poor diet quality in subjects was due to low consumption of nutrients and high consumption of fat. There is a correlation food selection and diet quality (p=0,034). There is no correlation  food purchase access (p=0,420), nutritional knowledge (p=0,283), and culture (p=0,301) with diet quality.Conclusion: There is a correlation food selection and diet quality, while there is no correlation access to food purchases, nutritional knowledge, and culture with diet quality.Keywords : diet quality; food choice; food purchase access; university students ABSTRAKLatar belakang: Pola makan masyarakat Indonesia mengalami perubahan karena pengaruh era globasilasi dan kemajuan teknologi. Perubahan pola makan yang tidak tepat seperti konsumsi makanan mengandung gula, garam, dan lemak yang berlebihan meningkatkan risiko obesitas. Kasus obesitas di Provinsi Jawa Tengah mengalami peningkatan dari tahun 2019 (5,5%) hingga 2021 (6,8%). Pola makan seseorang dapat mempengaruhi kuantitas dan kualitas makanan yang dikonsumsi sehingga berpengaruh terhadap kualitas diet.Tujuan: Tujuan penelitian adalah menganalisis hubungan pemilihan makanan dan akses pembelian makanan dengan kualitas diet.Metode: Penelitian ini merupakan penelitian observasional dengan desain cross-sectional. Subjek penelitian adalah mahasiswa Fakultas Kesehatan Masyarakat Universitas Diponegoro sebanyak 100 orang. Subjek dipilih dengan menggunakan metode simple random sampling. Variabel bebas penelitian ini adalah pemilihan makanan dan akses pembelian makanan. Variabel perancu penelitian ini adalah pengetahuan gizi dan budaya. Data kualitas diet berdasarkan hasil Semi Quantitative Food Frequency Questionnaire yang dikonversi ke skor kualitas diet. Analisis korelasi menggunakan uji Rank Spearman.Hasil: Subjek memiliki kualitas diet baik 55% dan kualitas diet kurang 45%. Kualitas diet kurang pada subjek disebabkan rendahnya asupan zat gizi dan konsumsi tinggi lemak. Terdapat hubungan pemilihan makanan dengan kualitas diet (p=0,034). Tidak ada hubungan akses pembelian makanan (p=0,420), pengetahuan gizi (p=0,283), dan budaya (p=0,301)  dengan kualitas diet.Simpulan: Terdapat hubungan pemilihan makanan dengan kualitas diet. Tidak ada hubungan akses pembelian makanan, pengetahuan gizi, dan budaya dengan kualitas diet mahasiswa.Kata Kunci : akses pembelian makanan; kualitas diet; mahasiswa; pemilihan makanan